2010
DOI: 10.1111/j.1469-8986.2010.01069.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of visual and verbal presentation on cognitive load in vigilance, memory, and arithmetic tasks

Abstract: Degree of pupil dilation has been shown to be a valid and reliable measure of cognitive load, but the effect of aural versus visual task presentation on pupil dilation is unknown. To evaluate effects of presentation mode, pupil dilation was measured in three tasks spanning a range of cognitive activities: mental multiplication, digit sequence recall, and vigilance. Stimuli were presented both aurally and visually, controlling for all known visual influences on pupil diameter. The patterns of dilation were simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
170
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(185 citation statements)
references
References 48 publications
14
170
0
1
Order By: Relevance
“…The main effect of presentation format (verbal only vs. verbal and visual) was significant across populations, such that individuals displayed superior memory recall when items were presented with a picture along with the verbal label compared to when presented with only a verbal label. This supports previous research suggesting that cognitive load is decreased when items are presented visually, as well as individuals benefitting from having both a verbal and a visual code for the items (Klingner, Tversky, & Hanrahan, 2011). The possibility should be acknowledged that participants may have performed better in the visual presentation condition due to increased practice, nevertheless, of main interest regarding the presentation manipulation was how presentation format interacted with the other manipulations, i.e., grouping/semantic relation, as discussed further on, as well as population.…”
Section: Discussionsupporting
confidence: 79%
“…The main effect of presentation format (verbal only vs. verbal and visual) was significant across populations, such that individuals displayed superior memory recall when items were presented with a picture along with the verbal label compared to when presented with only a verbal label. This supports previous research suggesting that cognitive load is decreased when items are presented visually, as well as individuals benefitting from having both a verbal and a visual code for the items (Klingner, Tversky, & Hanrahan, 2011). The possibility should be acknowledged that participants may have performed better in the visual presentation condition due to increased practice, nevertheless, of main interest regarding the presentation manipulation was how presentation format interacted with the other manipulations, i.e., grouping/semantic relation, as discussed further on, as well as population.…”
Section: Discussionsupporting
confidence: 79%
“…In addition to reliably demonstrating increased cognitive load with increasing question difficulty, pupillometry data have also shown that the modality of information presentation has cognitive loading effects. Using a remote eye tracker, Klingner, Tversky, and Hanrahan (2011) showed that cognitive load is higher for the same tasks when they are presented orally as opposed to visually. These experiments underscore the precision and expanded applications of this technique.…”
mentioning
confidence: 99%
“…Another remarkable property is that it is not affected by a participant's strategies, because it is quite difficult to control voluntarily. Due to these advantages, the pupillary response has been widely used in cognitive psychology to study a large variety of cognitive processes, including attention allocation (Karatekin, Couperus, & Marcus, 2004), face perception (Goldinger, He, & Papesh, 2009), arithmetic (Klingner, Tversky, & Hanrahan, 2011), and working memory (Heitz, Schrock, Payne, & Engle, 2008), among others.…”
mentioning
confidence: 99%